Pelatihan Pengelolaan Keuangan pada Kelompok Tani Sayuran di Desa Lingga Tiga - Novrihan Leily Nasution; Junita Lubis (Cakrawala: Jurnal Pengabdian Masyarakat Global, 2024)
One of the problems that often occurs in oil palm farmer groups is limited business development capital and financial management that is still not well organized. Based on these problems, the training implementation team raised the theme of financial management procedures in vegetable farmer groups in Lingga Tiga Village. The team will provide a simulation of making a feasibility proposal for a vegetable business and business and training in the preparation of vegetable business financial statements. By carrying out several programs in this training. It is hoped that farmers can improve the knowledge of financial management carried out by vegetable farmers.